Pengaruh Karakteristik Individu, Lingkungan Kerja Dan Kompetensi Terhadap Prestasi Kerja Pegawai Badan Pendapatan Daerah Kabupaten Labuhanbatu - Boy Rinaldi; Hasrudy Tanjung; Hazmanan Khair (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The purpose of this research is to determine and analyze the influence of individual characteristics on work performance, to determine and analyze the influence of the work environment on work performance, to determine and analyze the influence of competence on work performance and to determine and analyze the influence of individual characteristics, work environment and competence on performance works at the Labuhanbatu Regency Regional Revenue Agency. The approach used in this research is an associative approach. The population in this study was all employees of the Labuhanbatu Regency Regional Revenue Agency totaling 60 people and the sample used in this research was 60 people using a saturated sample. The data collection technique in this research used a questionnaire. The data analysis technique in this research uses Multiple Linear Regression, Classical Assumption Test, t Test and F Test, and Coefficient of Determination. Data processing in this research used the SPSS software program (version 24.00). Partially, individual characteristics have a significant influence on work performance. Partially, the work environment has a significant influence on work performance. Partially, competency has a significant influence on work performance. Simultaneously, individual characteristics, work environment and competence have a significant influence on employee work performance for employees of the Labuhanbatu Regency Regional Revenue Agency.